Analysis of Pronunciation Errors in Reading Arabic Language Texts: Case Study of Islamic Educational Management Students - Zahra Khusnul Lathifah; Siti Pupu Fauziah; Nova Monaya; Fikni Mutiara Rachma; Muhtadin Tyas; Warizal Warizal (Universitas Negeri Makassar, 2026)
This study investigates the types and causes of pronunciation errors in reading Arabic Texts among Islamic Educational Management students, with implications for their future roles in educational leadership. Employing a qualitative error analysis framework, the research utilized oral reading assessments, semi-structured interviews with instructors, and document analysis of student performance in sixth-semester Arabic for Education courses. Data were triangulated to identify recurrent phonological inaccuracies and contextualize them within pedagogical practices. Results demonstrated systematic misarticulation of Arabic phonemes, notably substituting kāf with qāf, zāy with jīm, ṭāʾ with tāʾ, ṣād with sīn, and khāʾ with ḥāʾ, particularly evident in readings from the book of Al-‘Arabiyyah Baina Yadaik. These errors were attributed to three interrelated factors: phonological interference from the students’ native language, which lacks equivalent Arabic sounds; insufficient emphasis on phonetic training in course instruction; and limited immersive exposure to authentic Arabic speech. The findings highlight critical implications, as precise Arabic pronunciation is integral to effective communication in Islamic educational leadership, where textual accuracy and oral proficiency are essential for pedagogical and administrative credibility. Consequently, this study advocates for curriculum reforms prioritizing phonemic awareness through targeted articulatory exercises and immersive listening modules, ensuring graduates possess the linguistic precision required to uphold educational quality in madrasas and Islamic boarding schools. Such adjustments would bridge the gap between theoretical language acquisition and functional communicative competence, aligning academic training with professional demands.